2011
DOI: 10.1007/s11244-011-9695-9
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Hydrogenation Studies on Co and CoPt Bimetallic Nanoparticles Under Reaction Conditions Using TEM, XPS and NEXAFS

Abstract: . (2011) 'CO2 hydrogenation studies on Co and CoPt imetallic nanoparticles under reaction conditions using TEM, XPS and NEXAFS.', Topics in catalysis., 54 (13-15). pp. 778-785. Further information on publisher's website:http://dx.doi.org/10.1007/s11244-011-9695-9Publisher's copyright statement:The nal publication is available at Springer via http://dx.doi.org/10.1007/s11244-011-9695-9.Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
107
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(114 citation statements)
references
References 23 publications
5
107
0
Order By: Relevance
“…We identified this was attributable to platinum segregating to the surface in reducing conditions as demonstrated by ambient pressure X-ray photoelectron spectroscopy and environmental transmission electron microscopy in H 2 . 3 Here, we identify a different, more realistic model for the catalyst structure involved in the Pt promotional effect. Instead of the two metals being present within a single nanoparticle, we have instead taken discrete monometallic nanoparticles of both Pt and Co and deposited them in close proximity within the pores of a mesoporous silica, MCF-17.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified this was attributable to platinum segregating to the surface in reducing conditions as demonstrated by ambient pressure X-ray photoelectron spectroscopy and environmental transmission electron microscopy in H 2 . 3 Here, we identify a different, more realistic model for the catalyst structure involved in the Pt promotional effect. Instead of the two metals being present within a single nanoparticle, we have instead taken discrete monometallic nanoparticles of both Pt and Co and deposited them in close proximity within the pores of a mesoporous silica, MCF-17.…”
Section: Introductionmentioning
confidence: 99%
“…This is slightly more than the often < 1:100 molar ratio found in commercial type catalysts to allow us to characterize the Pt nanoparticles present with a range of techniques. We have previously demonstrated that the pure Pt nanoparticles are inactive for this reaction, 3 therefore we assume that all CH 4 production is derived from the pure Co particles. The dramatic increase in rate is therefore the result of platinum nanoparticles enhancing the activity of the cobalt.…”
Section: Introductionmentioning
confidence: 99%
“…The Pt then covers the particle surface as shown in Figure 4. 82 These Pt encapsulated particles were found to be completely inactive for CO 2 hydrogenation. 82 It was reported that preparing nanoparticles of consistently low Pt concentration is synthetically very difficult owing to their segregation into particles with and without Pt.…”
Section: Precious Metal Promotion Effects Studied Using Nanomaterialsmentioning
confidence: 99%
“…[1][2][3] This has largely arisen out of their size dependent properties, ease of preparation for FT active metals and large number of atoms at their surface. Despite the development in a number of chemical approaches 4 that give control over particle size and composition, and the subsequent assemblage of these preformed particles onto supports, 5 very few literature examples involving the addition of preformed nanoparticles to support materials exist.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the development in a number of chemical approaches 4 that give control over particle size and composition, and the subsequent assemblage of these preformed particles onto supports, 5 very few literature examples involving the addition of preformed nanoparticles to support materials exist. 3,6,7 This method is highly advantageous as it allows greater control over what species are assembled onto a support material and it removes the dispersion problems seen with metal clusters in traditional FT catalysts. 8 Further research is required to develop new systems based on the assemblage of preformed particles onto supports so that an assessment of the benefits of these materials can be made.…”
Section: Introductionmentioning
confidence: 99%